Highly-automated, high-throughput replication of yeast-based logic circuit design assessments. Issue 1 (6th October 2022) - Goldman, Robert P; Moseley, Robert; Roehner, Nicholas; Cummins, Breschine; Vrana, Justin D; Clowers, Katie J; Bryce, Daniel; Beal, Jacob; DeHaven, Matthew; Nowak, Joshua; Higa, Trissha; Biggers, Vanessa; et al.
Abstract: We describe an experimental campaign that replicated the performance assessment of logic gates engineered into cells of Saccharomyces cerevisiae by Gander et al. Our experimental campaign used a novel high-throughput experimentation framework developed under Defense Advanced Research Projects Agency's Synergistic Discovery and Design program: a remote robotic lab at Strateos executed a parameterized experimental protocol. Using this protocol and robotic execution, we generated two orders of magnitude more flow cytometry data than the original experiments. We discuss our results, which largely, but not completely, agree with the original report and make some remarks about lessons learned. Graphical Abstract